Interpersonal relations in the Thought of Marcel and Levinas: from Intersubjectivity to Otherness - Urabayen, Julia (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article is a reflection on a key theme in some of today’s most important philosophical currents: interpersonal relations. In the 20th century many thinkers opted for a different treatment of the person, and especially his or her openness to others. The approach taken in this article will throw light on the confluence of diverse postures and, at the same time, will offer a good starting point for clarifying fundamental differences that separate certain philosophers who, in principle, appear to be very close. Specifically, the objective of this article is to analyze the philosophies of Marcel and Lévinas, showing that, despite what they have in common, their anthropologies are very different. While Marcel holds that anthropology is linked to ontology, although not dependent upon it, Lévinas proposes that ethics should become first philosophy. As a result, for Marcel human relations are intersubjective, while for Lévinas the only way to treat of the human being is via otherness.
Keywords: Marcel; Levinas; intersubjectivity; otherness